Therapeutic effect of insulin in reduction of critical illness polyneuropathy and Myopathy in pediatric intensive care unit - BILAN, nemat; SADEGVAND, Shahram; RANJBAR, Shirin (Iranian Journal of Child Neurology, 2012)
How to Cite this Article: Fayyazi A, Karimzadeh P, Torabian S, Damadi S, Khaje A. Comparison of Intravenous Midazolam Drip with Intermittent Intravenous Diazepam in The Treatment of Refractory Serial Seizures in Children. Iran J Child Neurol 2012; 6(3): 15-19. Objective Hyperglycemia may occur in the patients affected by any kind of critical illness.This complication makes an adverse effect on the clinical outcome of thesepatients by causing polyneuropathy and myopathy. It has been recently shownthat treatment of hyperglycemia with insulin administration significantly reducesthe prevalence of critical illness polyneuropathy and myopathy (CIPNM) andon the other hand reduces the demand for long-term mechanical ventilation inthe patients admitted to the ICU for more than 1 week. The aim of this studywas to determine the therapeutic effect of insulin in reducing the incidence ofCIPNM in the pediatric intensive care unit (PICU). Materials & Methods In this study, we recruited 30 patients admitted to the PICU of Tabriz PediatricHospital. The incidence of CIPNM following hyperglycemia was evaluated inthese patients. The patients were categorized into two groups. In the case group,blood sugar was controlled in the range of 140-180mg/dl by administration of0.05 unit per kilogram body weight of insulin as drip protocol in an hour and inthe control group, placebo was used. Consequently, the incidence of CIPNM,duration of PICU and duration of mechanical ventilation were comparedbetween the two groups. Results The incidence of CIPNM and duration of PICU stay and mechanical ventilationwere significantly reduced in the patients treated with insulin compared to thecontrol group. Conclusion This study shows that blood sugar control decreases the incidence of CIPNM. References Van den Berghe G. Insulin therapy in critical illness. Can J Diabetes. 2004;28(1):43-9. Bolton CF, Gilbert JJ, Hahn AF, Sibbald WJ.Polyneuropathy in critically ill patients. J Neurol Neurosurg Psychiatry. 1984 Nov;47(11):1223-31. Vondracek P, Bednarik J. Critical and electrophysiological findings and long-term outcomes in pediatric patients with critical illness polyneuropathy. Eur J Pediatr Neurol 2006 Jul;10(4):176-81. Witt NJ, Zochodne DW, Bolton CF, Grand’Maison F, Wells G, Young GB et al. Peripheral nerve functionin sepsis and multiple organ failure. Chest 1991 Jan;99(1):176-84. 5. Marino PL. The ICU book. 2nd ed. Philadelphia:Lippincott Williams and Wilkins; 1998. p. 800-1. Hermans G, De Jonghe B, Bruyninckx F, Van den BergheG. Clinical review: Critical illness polyneuropathy and myopathy. Crit Care 2008;12(6): 238. Wiener RS, Wiener DC, Larson RJ. Benefits and risks of tight glucose control in critically ill adults: a meta analysis.JAMA 2008 Aug;300(8):933-44. 8. Griesdale DE, de Souza RJ, van Dam RM, Heyland DK,Cook DJ, Malhotra A et al. Intensive insulin therapy and mortality among critically ill patients: a meta-analysis including NICE-SUGAR study data. CMAJ 2009 Apr;180(8):821-7. Mraovic B. Continuous glucose monitoring during intensive insulin therapy. J iabetes Sci Technol 2009 Jul;3(4):960-3. De Jonghe B, Bastuji-Garin S, Sharshar T, Outina,H, Brochard L. Does ICU-acquired paresis lengthen weaning from mechanical ventilation? Intensive Care Med 2004 Jun;30(6):1117-21. Garnacho-Mantero J, Amaya-Villar R, García-Garmendía JL, Madrazo-Osuna J, Ortiz-Leyba C. Effects of criticallillness polyneuropathy on the withdrawal from mechanical ventilation and the length of stay in septic patients. CritCare Med 2005 Feb;33(2):349-54.